2021
DOI: 10.31925/farmacia.2021.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Involvement in Drug-Induced Gingival Overgrowth

Abstract: Gingival overgrowth is an undesirable and well-recognized side effect following the use of various drugs, such as phenytoin, nifedipine and cyclosporine A (CsA). Apoptosis constitutes a necessary process for constant tissue remodelling, its absence playing a critical role in gingival overgrowth. The aim of this study was to evaluate the effects of THP (thapsigargin), brefeldin A, cyclopiazonic acid, and capsaicin on the endoplasmic reticulum (ER) and their involvement in apoptosis of normal fibroblasts compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Nonetheless, these changes were not as pronounced as those observed with electronic cigarette-derived nicotine (Figure 4). According to the results of the study, the cell morphology displayed changes similar to those observed in the present study, indicating that apoptosis is involved [38]. Another study evaluating the potential effects of nicotine on human embryonic stem cell (hESC) line H9 observed morphological changes that affected cardiogenic differentiation of hESCs [20].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Nonetheless, these changes were not as pronounced as those observed with electronic cigarette-derived nicotine (Figure 4). According to the results of the study, the cell morphology displayed changes similar to those observed in the present study, indicating that apoptosis is involved [38]. Another study evaluating the potential effects of nicotine on human embryonic stem cell (hESC) line H9 observed morphological changes that affected cardiogenic differentiation of hESCs [20].…”
Section: Resultssupporting
confidence: 78%
“…Results from the study were similar to those obtained in the present study, indicating that nicotine inhibits cell viability dose-dependently. Furthermore, it was noted that Nic induces cell apoptosis, resulting in a reduction in anti-apoptotic gene expression and an increase in pro-apoptotic gene expression [38]. According to the study conducted by Basma and colleagues regarding the effects of nicotine from electronic cigarettes, it is shown that it has a strong cytotoxic effect on cardiomyocytes, increasing the production of reactive oxygen species and altering genes involved in cell proliferation and apoptosis [3].…”
Section: Resultsmentioning
confidence: 99%